PENERAPAN HASIL PENELITIAN PSIKOEDUKASI DALAM PENURUNAN MASALAH PSIKOSOSIAL KELUARGA PASCA BENCANA DI MASYARAKAT SEBAGAI UPAYA PROMOTIP, PREVENTIP, KURATIP DAN REHABILITATIP DI DUSUN JEMBLUNG, DESA SAMPANG, KECAMATAN KARANGKOBAR, KABUPATEN BANJARNEGARA - Erna Erawati; Suharsono Suharsono; Suyanta Suyanta; Wiwin Reni Rachmawati; Siti Arifah; Moh Hanafi (Jurnal LINK, 2016)
As a part of management disaster, the intervention of psycho education has been done by a nurse in Diploma IV nursing program as dedication to community. The aims of  dedication to community is to explore the effect of psycho education among survivor of landslide in Banjarnegara in decreasing psychosocial problem. Method: We used psycho education as intervention and After implementation for 50 hours with technique of focus group discussion there was a significant decrease in psychosocial problem among family with survivor of landslide. We recommended that psycho education become of disaster management.